Buraco negro de Dymnikova em N dimensões - Macêdo, Matheus Henrique de Sousa (2025)
In this study, we investigate the regular Dymnikova black hole in N dimensions, analyzing its regularity, thermodynamic properties, and stability. Our objective is to verify the absence of singularities, evaluate the energy conditions, and assess the stability of the black hole. We use the curvature invariant and tensors to test regularity, as well as the WKB method for quasi-normal modes. The results show that the solution is regular, but violates certain energy conditions in a region close to the core. Additionally, the thermodynamic analysis indicates that the black hole exhibits thermal stability in certain regions of space. Meanwhile, the quasi-normal modes reveal the stability of the solution against scalar perturbations. Since the Dymnikova solution is a vacuum solution that includes the Schwarzschild–de Sitter metric, our findings provide insights for future investigations in modified gravity and reinforce the viability of this solution.